Symptomatic Histologically Proven Necrosis of Brain following Stereotactic Radiation and Ipilimumab in Six Lesions in Four Melanoma Patients - Stephanie Du Four; Angela Hong; Matthew Chan; Michail Charakidis; Johnny Duerinck; Sofie Wilgenhof; Wei Wang; Linda Feng; Alex Michotte; Meena Okera; Brindha Shivalingam; Gerald Fogarty; et al. (Case Reports in Oncological Medicine)
Four cases previously treated with ipilimumab with a total of six histologically confirmed symptomatic lesions of RNB without any sign of active tumour following stereotactic irradiation of MBM are reported. These lesions were all originally thought to be disease recurrence. In two cases, ipilimumab was given prior to SRT; in the other two ipilimumab was given after SRT. The average time from first ipilimumab to RNB was 15 months. The average time from SRT to RNB was 11 months. The average time from first diagnosis of MBM to last follow-up was 20 months at which time three patients were still alive, one with no evidence of disease. These cases represent approximately three percent of the total cases of melanoma and ten percent of those cases treated with ipilimumab irradiated in our respective centres collectively. We report this to highlight this new problem so that others may have a high index of suspicion, allowing, if clinically warranted, aggressive surgical salvage, possibly resulting in increased survival. Further studies prospectively collecting data to understand the denominator of this problem are needed to determine whether this problem is just the result of longer survival or whether there is some synergy between these two modalities that are increasingly being used together.